1940
DOI: 10.1085/jgp.23.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of the Proteolytic Enzyme From the Latex of the Milkweed, Asclepias Speciosa Torr. Some Comparisons With Other Proteases

Abstract: 1. A study has been made of the properties of a hitherto unreported proteolytic enzyme from the latex of the milkweed, Asclepias speciosa. The new protease has been named asclepain by the authors. 2. The results of chemical, diffusion, and denaturation tests indicate that asclepain is a protein. 3. Like papain, asclepain dots milk and digests most proteins, particularly if they are dissolved in concentrated urea solution. Unlike papain, asclepain did not clot blood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1952
1952
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 4 publications
1
13
0
1
Order By: Relevance
“…Winnick, Davis and Greenberg observed that the rate of bromelain inactivation follows a first order reaction at 55 and 60°C; however, at temperatures above 70°C, the destruction of enzyme is not a first order reaction. The process of bromelain thermal denaturation studied by circular dichroism (CD), and differential scanning calorimetry (DSC) is completely irreversible and apparently follows a simple two‐stage mechanism, where an intermediate exists between the native and denatured states …”
Section: Stabilitymentioning
confidence: 99%
“…Winnick, Davis and Greenberg observed that the rate of bromelain inactivation follows a first order reaction at 55 and 60°C; however, at temperatures above 70°C, the destruction of enzyme is not a first order reaction. The process of bromelain thermal denaturation studied by circular dichroism (CD), and differential scanning calorimetry (DSC) is completely irreversible and apparently follows a simple two‐stage mechanism, where an intermediate exists between the native and denatured states …”
Section: Stabilitymentioning
confidence: 99%
“…Both are members of Asclepiadaceae family. There are both inhibited by cysteine-specific inhibitors (e. g., iodoacetic-acid) [55]. Calotrop(a)ins DI, DII, FI, FII: There are at least four cysteine proteases purified from the latex of Calotropis gigantea (L.) Dryand.…”
Section: Morrenain O IImentioning
confidence: 99%
“…The latex of the Asclepiadaceae plant family usually contains proteases. Studies were made on few genera such as Asclepias (Barragán et al, 1985;Brockbank and Lynn, 1979;Carpenter and Lovelace, 1943;Greenberg and Winnick, 1940;Lynn et al, 1980;Tablero et al, 1991;Winnick et al, 1940) and Calotropis Joshi, 1979a, 1979b;Pal and Sinha, 1980;Sengupta et al, 1984). Recently, some cysteine proteases from plants belonging to this family were purified and characterized in our laboratory from the latex of Morrenia brachystephana and Morrenia odorata (Arribére et al, 1998;Vairo Cavalli et al, 2001, Araujia hortorum (Obregón et al, 2001;Priolo et al, 2000), and Asclepias fruticosa (Trejo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%